A Century of Elk Restoration in Eastern North America. Issue 6 (November 2014) - Popp, Jesse N.; Toman, Tom; Mallory, Frank F.; Hamr, Josef
Abstract Over a century has passed since elk were extirpated in eastern North America. During that time, numerous attempts to reintroduce elk into eastern North America have resulted in varying degrees of success and failure. An overview of restoration efforts during the last 100 years is presented here with emphasis on the differences in rates of population change among regions and differences in major causes of elk mortality during both the pre‐ and post‐acclimation periods. Approximately 40% of recorded elk reintroduction attempts in eastern North America resulted in failure with the majority of these having occurred in the first half of the 20th century. Although rates of population change in elk were highly variable, they were not related to founding population size. Major causes of mortality varied among regions and should be considered in future reintroduction attempts.